2002
DOI: 10.1016/s0002-9440(10)61119-4
|View full text |Cite
|
Sign up to set email alerts
|

Tau and α-Synuclein Pathology in Amygdala of Parkinsonism-Dementia Complex Patients of Guam

Abstract: Amyotrophic lateral sclerosis/parkinsonism-dementia complex (ALS/PDC) is a progressive neurodegenerative disorder of Chamorro residents of Guam and the Mariana Islands, characterized by abundant neuron loss and tau neurofibrillary pathology similar to that observed in Alzheimer's disease (AD). A variety of neurodegenerative diseases with tau pathology including ALS/PDC also have alpha-synuclein positive pathology, primarily in the amygdala. We further characterized the tau and alpha-synuclein pathology in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 46 publications
(55 reference statements)
2
51
1
Order By: Relevance
“…One group used an extraction protocol similar to ours to show insoluble forms of SNCA in the amygdala only in those PDC patients with SNCA-immunoreactive inclusions. 55 In contrast to these findings in regions of brain with unclear relevance to the clinical manifestations of PDC, our quantitative data demonstrated the accumu- lation of abnormally hydrophobic SNCA in frontal and temporal cortex of patients with PDC to levels comparable with DLB despite the lack of LB accumulation in these regions of brain that are clearly related to cognitive function. Others have presented elegant data demonstrating interactions between SNCA and tau 57 ; however, we think this is an unlikely explanation for PDC because although AD, PSP, and PDC had increased SI and TI tau, only PDC had significantly increased TI SNCA.…”
Section: Discussioncontrasting
confidence: 95%
“…One group used an extraction protocol similar to ours to show insoluble forms of SNCA in the amygdala only in those PDC patients with SNCA-immunoreactive inclusions. 55 In contrast to these findings in regions of brain with unclear relevance to the clinical manifestations of PDC, our quantitative data demonstrated the accumu- lation of abnormally hydrophobic SNCA in frontal and temporal cortex of patients with PDC to levels comparable with DLB despite the lack of LB accumulation in these regions of brain that are clearly related to cognitive function. Others have presented elegant data demonstrating interactions between SNCA and tau 57 ; however, we think this is an unlikely explanation for PDC because although AD, PSP, and PDC had increased SI and TI tau, only PDC had significantly increased TI SNCA.…”
Section: Discussioncontrasting
confidence: 95%
“…Sections were then lightly counterstained with hematoxylin, dehydrated, and coverslipped. Double-labeling immunofluorescence analyses were performed as previously described 24 using Alexa Fluor 488-and 594-conjugated secondary antibodies (Molecular Probes, Eugene, OR) and coverslipped with Vectashield-DAPI mounting medium (Vector Laboratories).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Findings from several recent studies have suggested that aggregationprone proteins, such as tau, α-syn, polyglutaminecontaining proteins, and amyloid-β, can enhance each other's aggregation [30][31][32][33][34][35]. In particular, β-amyloid augments α-syn accumulation [33,34], Tau increases α-syn aggregation [31,32] while synergistic interactions between β-amyloid, tau, and α-syn might accelerate neuropathology [33]. Importantly, mechanism of hybrid oligomer formation plays an essential role in the pathogenesis of combined AD and PD [30].…”
Section: Discussionmentioning
confidence: 99%